You would do like you did, and get 6+y except you would make it equal to zero (6+y=0) and then subtract 6 from each side so y = -6
Here's what you do if you want to check your answer:
You want to plug -6 back into everywhere you see a y in the AD equation (2x+y) So now you have 2x-6. Then you want to solve for x. 2x-6=0 Add six to both sides to get rid of the -6 on the left. 2x=6 Then divide both sides by two to get rid of the multiplication on the left side. x=3. So you know it's right because that's what the original equation told you!
Hope I helped! :]
2007-10-01 10:59:04
·
answer #1
·
answered by Allison 2
·
0⤊
1⤋
AD = 8
This problem is a little hard to answer as you state it. However, I believe you are looking at a rectangle (or a square which is, of course, also a rectangle) labeled in the common fashion of starting at one corner and labeling A-B-C-D as one goes around. If so, AD and BC are opposing sides of the rectangle/square and therefore are equal in length so the values given for their lengths are also equal.
If so, then 2x + y = 7y - 2x. Rearranging to get the y's by themselves and then to end up with only "y =" (remember, we already know x = 3), we add 2x to each side, subtract y from each side and divide by 6:
2x + y + 2x = 7y - 2x + 2x
4x + y - y = 7y - y
4x / 6 = 6y / 6
(2/3)x = y
(2/3) * 3 = y
y = 2
So, if x = 3 and y = 2, and AD = 2x + y, then AD = 2*3 + 2 = 8.
So, looking at the secondary question you asked, yes, you did it right, AD does equal 6 + y. And the trick to finding what 6 + y equals is in the information not included in the statement of the problem. If there really is nothing else, then it is NOT possible to find 6 + y as equalling some particular value rather than as a line on a graph.
2007-10-01 18:06:37
·
answer #2
·
answered by bimeateater 7
·
0⤊
0⤋
Let's set AD = Q, and BC = W
It will make things look a little simpler, and it's more clear what you are dealing with.
Q = 2x
W = 7y - 2x
Where x = 3
You have 4 unknowns and only 2 equations. There's no way you will ever solve for 'AD'...which we called Q.
And yes, you are thinking along the correct lines.
The best you can hope for is the following:
Q = 2*3
==> Q = AD = 6
You don' even need 'BC'. I think there's some information missing, maybe even whole equations missing from this problem. But anyway, this is all you can do with this.
Hope this helps you.
2007-10-01 18:05:00
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
You need one more restriction, or you can represent AD as a function of BC.
AD
= 6 + y
= 6+ (BC+6)/7
= BC + 6 6/7
2007-10-01 17:57:24
·
answer #4
·
answered by sahsjing 7
·
0⤊
0⤋
I'm assuming BC is some unknown number you will include in your answer.
So if x=3, then BC=7y-6
solve for y
BC+6=7y
y=(BC+6)/7
now AD=2(3)+(BC+6)/7
AD= (BC+48)/7
does this look like what you are looking for?
2007-10-01 17:58:17
·
answer #5
·
answered by erikoo7 3
·
0⤊
0⤋
AD = 2x+y = 6+y
BC = 7y -2x = 7y-6
AD +BC = 8y
AD = 8y -BC
2007-10-01 17:59:49
·
answer #6
·
answered by ironduke8159 7
·
0⤊
0⤋
It doesn't matter what "6 + y" equals because you answered the question "find AD".
2007-10-01 18:00:13
·
answer #7
·
answered by Mathsorcerer 7
·
0⤊
0⤋
I recommend asking your teacher before class starts.
2007-10-01 18:00:33
·
answer #8
·
answered by collestkidondablock 1
·
0⤊
1⤋
iT IS IMPOSSIBLE TO SOLVE.
2007-10-01 17:59:09
·
answer #9
·
answered by thiru 3
·
0⤊
1⤋